An update on the impact of food allergy on anxiety and quality of life. Issue 4 (August 2017) - Shaker, Marcus S.; Schwartz, Jonathan; Ferguson, Morgan
Abstract : Purpose of review: Food allergies have become more common, and management involves dietary avoidance that can impair quality of life. Patients and families must manage the daily risk of anaphylaxis at each meal. The purpose of this review is to describe the impact of food allergies on quality of life and to provide an update on new developments in food allergy management, particularly peanut allergy. Recent findings: Food allergy requires careful avoidance of common and ubiquitous dietary allergens. Living with food allergy is associated with annual economic costs in excess of 4000 per child, in addition to risks of anxiety and depressive symptoms. An expert panel sponsored by the 2017 National Institute of Allergy and Infectious Diseases published addendum guidelines for the prevention of peanut allergy, which suggest three separate approaches to peanut protein introduction for infants at various levels of risk. Summary: Clinicians must be aware of underappreciated burdens faced by children and families with food allergies. Management involves a partnership between primary and specialty care. Mitigation strategies to improve quality of life for patients include efforts to avoid overdiagnosis in synergy with balanced counseling about the risks of food allergies. Experimental food allergen desensitization can improve quality of life but remains investigational at this time. For patients with significant anxiety, interdisciplinary management involving professional counseling may be helpful. Risk stratification and early introduction of peanut protein can help prevent the development of peanut allergy.